2005
DOI: 10.1103/physreve.71.011913
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of opening-up vesicles with single and two holes

Abstract: Cuplike lipid vesicles with a single hole and tubelike vesicles with two holes were theoretically analyzed by taking into account the line tension of membrane holes and the bending energy of membranes, using the area difference elasticity model. We numerically solved the Euler-Lagrange equation and the boundary conditions holding on the membrane edge to obtain axisymmetric vesicle shapes that minimize the total energy. The numerical results showed that when the line tension is very low, and for appropriate val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 22 publications
4
43
0
Order By: Relevance
“…However, the behavior of membranes with edges depends on . 56,57 In the meshless membrane model, and ⌫ can essentially be varied independently. 42 The bending rigidity increases linearly with k ␣ and is almost independent of , with…”
Section: Membrane Propertiesmentioning
confidence: 99%
“…However, the behavior of membranes with edges depends on . 56,57 In the meshless membrane model, and ⌫ can essentially be varied independently. 42 The bending rigidity increases linearly with k ␣ and is almost independent of , with…”
Section: Membrane Propertiesmentioning
confidence: 99%
“…Theoretically, opening-up shapes can only be established when the spontaneous curvature, as well as the line tension, is within a certain range. [14] Furthermore, some other combinations cause inside-out topological inversion of vesicles, [2] which suggests a large negative spontaneous curvature. It has been reported that some detergents (including Triton X-100) are able to accelerate phospholipid flip-flop.…”
mentioning
confidence: 99%
“…The general solution of this formidable problem is very difficult and several papers dealing with this issue have been written over the time. [25][26][27][28][29] Here, we follow a simple approximate procedure that retains most of the relevant physics. A similar procedure, that does not include the relevant spontaneous curvature effects, has been developed some time ago.…”
Section: A Modeling the Planar To Curved Bilayer Transitionmentioning
confidence: 99%